3D Bioprinting: Lipid‐Bilayer‐Supported 3D Printing of Human Cerebral Cortex Cells Reveals Developmental Interactions (Adv. Mater. 31/2020). Issue 31 (4th August 2020) - Zhou, Linna; Wolfes, Anne C.; Li, Yichen; Chan, Danny C. W.; Ko, Ho; Szele, Francis G.; Bayley, Hagan
Abstract : Current understanding of brain development, derived from suboptimal in vitro and animal models, is rudimentary. In article number 2002183, Francis G. Szele, Hagan Bayley, and co‐workers introduce a means to print human neural cells in a soft, biocompatible extracellular matrix. The approach provides precise, customizable construction of natural and unnatural patterns of cells, and yields important insights into the development of the human cerebral cortex.